Deposition and Tribological Properties of Sulfur-Doped DLC Films Deposited by PBII Method - Nutthanun Moolsradoo; Shuichi Watanabe (Advances in Materials Science and Engineering)
Sulfur-doped diamond-like carbon films (S-DLC) fabricated from C2H2 and SF6 mixtures were used to study the effects of sulfur content and negative pulse bias voltage on the deposition and tribological properties of films prepared by plasma-based ion implantation (PBII). The structure and relative concentration of the films were analyzed by Raman spectroscopy and Auger electron spectroscopy. Hardness and elastic modulus of films were measured by nanoindentation hardness testing. Tribological characteristics of films were performed using a ball-on-disk friction tester. The results indicate that with the increasing sulfur content, the hardness and elastic modulus decrease. Additionally, by changing the negative pulse bias voltage from 0 kV to −5 kV, the hardness and elastic modulus increase, while the friction coefficient and specific wear rate tends to decrease. Moreover, at a negative pulse bias voltage of −5 kV and flow-rate ratio of 1 : 2, there is considerable improvement in friction coefficient of 0.05 under ambient air is due to the formation of a transfer films on the interface. The decrease in the friction coefficient of films doped with 4.9 at.% sulfur is greater under high vacuum (0.03) than under ambient air (>0.1).